Tunisia Economic Monitor, Summer 2020 : The COVID-19 Global Pandemic Shock - World Bank (World Bank, Washington, DC, 2021)
The Tunisia Economic Monitor provides an update on key economic developments and policies. It examines these economic developments and policies in a longer-term and global context and assesses their implications for the outlook for the country. There are two special focus sections in this edition of the Tunisia Economic Monitor. The first discusses the macroeconomic impact of the COVID-19 (coronavirus) pandemic on the Tunisian economy and the second presents findings from a diagnostic of Tunisia’s infrastructure sectors (transport, electricity, water and sanitation, and information and communication technology) carried out by the World Bank in collaboration with the Government of Tunisia.